Transformasi Administrasi Bisnis Melalui Penerapan Teknologi Cloud pada Koperasi Desa - Naqiya, Alfina Zsazsa; Masditok, Tokit; Muklisin, Sanitra; Rozi, Fakhrur (Devotion: Journal Corner of Community Service, 2024)
This community service focuses on strengthening local governance and empowering coastal communities in Sebesi Island, Lampung Selatan. The subject of devotion involves village officials, youth groups, and micro-entrepreneurs who play a strategic role in sustainable development. The main purpose of this program is to enhance administrative capacity, improve community participation, and support economic resilience through education and training. The method applied is a participatory approach, combining socialization, workshops, focus group discussions, and mentoring to ensure inclusiveness and effectiveness. The strategy emphasizes collaboration between universities, local government, and community members to foster sustainable governance practices. The results show increased awareness of administrative accountability, better community engagement in decision-making, and strengthened economic initiatives, particularly in small-scale businesses. This service demonstrates that integrated approaches linking governance, education, and empowerment can significantly contribute to social change and the improvement of village administration quality.